A critical review of autopsy findings in deaths due to COVID-19 - Nayak, Gyanaranjan; Pradhan, Sujita; Nayak, Lopamudra; Sahoo, Niranjan (International Journal of Research in Medical Sciences, 2024)
Not much is known about the pathological post-mortem findings of people dying of the novel coronavirus disease. There is a great need of such information for better clinical management of COVID-19 cases. A detailed literature search was conducted followed by its critical review. The search was made in databases like Pub Med, Scopus and EMBASE. The histopathological alterations were found to be mainly confined to the lungs. This included diffuse alveolar damage with formation of hyaline membrane and pulmonary microvascular thrombosis. There was a high incidence of deep venous thrombosis and pulmonary embolism in COVID-19 patients which hints towards possible endothelial involvement. The findings of the review have been derived from very few and restricted studies. These claims need to be substantiated by doing further studies.